Текстовий концепт-константа Подорож: просторові параметри (на матеріалі творів Ле Клезіо) - Каратєєва, Ганна Михайлівна; Karatieyeva, H. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зроблено спробу розкрити та дослідити основні лінгвокогнітивні характеристики просторових параметрів розгортання текстового концепту-константа подорож, який, як і будь-яке переміщення в реальності, передбачає просторове обрамлення. Проведений лексико-семантичний та лінгвокогнітивний аналіз просторових локусів, крізь які постійно переміщується головний суб’єкт прози Ле Клезіо, дав нам змогу виявити та дослідити основні текстові компоненти мовного втілення просторових параметрів ле-клезіанської подорожі, виділити їх основні семантичні й концептуальні ознаки, простежити особливості розгортання текстового концепту-константи подорож у межах виокремлених просторових зон, тобто локусів. The article is an attempt to discover and investigate the main linguo-cognitive features of spatial parameters of developing of the textual concept-constant journey. Lexico-semantic and linguo-cognitive analysis of spatial locuses used by the main subject of Le Cl?zio’s prose for journeys was made. The results helped us to indicate and investigate the main textual components of linguistic objectification of Le Cl?zian journey, as well as to define their main conceptual and semantic characteristics, to observe specifics of the textual concept-constant journey‘s development within the framework of concrete locuses. It has been discovered that main subjects of Le Cl?zio’s prose usually journey by two basic locuses: natural environment and urban environment. It has been found that in the author’s prose the locus urban environmentis conceptualized as a negative entity (concepts darkness, war, civilization evil, mechanicism), even having an occasional positive lexico-semantic description. The locus natural environment traditionally is implemented in concepts which bring positive connotation (light, peace, myth, life).
Textual Concept-Constant Journey: Parameters of Space (based on Le Cl?zio’s Prose)
Keywords: текстовий концепт-константа; textual concept-constant; головний суб’єкт; main subject; вербалізація; verbalization